Case Report: Hypertrophic cardiomyopathy with recurrent episodes of ventricular fibrillation and concurrent sinus arrest - Hamidi, Jassin; Winter, Joachim; Weber, Rene; Dittmann, Sven; Schulze-Bahr, Eric (Frontiers in Cardiovascular Medicine, 2023)
HCM hypertrophic cardiomyopathy hiPSCs human induced pluripotent stem cells HRV heart rate variability ICD implantable cardioverter-defibrillator LV left ventricular LVNC left ventricular non-compaction LVOT left ventricular outflow tract NGS next generation sequencing SACT sinoatrial conduction time SAN sinoatrial node SCA sudden cardiac arrest S-ICD subcutaneous ICD SNRT sinus node recovery time SR sarcoplasmic reticulum TSH Thyroid-stimulating hormone VES ventricular extrasystoles VF ventricular fibrillation